Public key suppression and recovery using a PANDA ring resonator for high security communication - Juleang, Pakorn; Phongsanam, Prapas; Mitatha, Somsak; Yupapin, Preecha P. (My University, 2011)
An interesting security technique that uses the dark-bright soliton conversion control within the microring resonator is proposed. The obtained outputs for a dark-bright soliton dynamic state can be controlled and used to form the public key suppression for communication security application. However, a good design should be possible to be fabricated; therefore, by using the parameters based on the practical device parameters, the simulation results obtained have shown that the proposed system can indeed be achieved. The public key suppression and public key recovery can be used in a highly secure communication system and has potential applications in optical cryptography. © 2011 Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: communication security; PANDA ring resonator; signal recovery; signal suppression